Towards in-flight temperature monitoring for nozzle guide vanes using ultrasonic guided waves - Yule, Lawrence M.; Zaghari, Bahareh; Harris, Nicholas; Hill, Martyn (AIAA, 2021)
The temperature monitoring of nozzle guide vanes is a challenging task due to the extreme temperatures, gas pressures, and cramped conditions of aero-engines. Ultrasonic guided waves are an attractive method of temperature monitoring as the sensors can be placed outside of the gas path without influencing component operation. In this paper the suitability of using ultrasonic guided waves in the form of the S0 Lamb wave mode is investigated by comparing experimentally measured wave velocity change with temperature against theoretical wave velocity extracted from dispersion curves. Waves are transmitted through an aluminium plate using a pitch-catch wedge transducer configuration, and wave velocity is measured using across-correlation function. Temperature is controlled with a hot plate from room temperature to 100°C, and monitored using thermocouples. Results show that this transducer configuration is capable of monitoring a change in temperature based on a change in wave velocity, showing a good agreement with theoretical predictions, within 4.89+/-2.27 m/s on average. The temperature sensitivity of the system is 1.26–1.78 m/s/°C over the range 24°C–94°C. This shows the potential for a guided wave based temperature monitoring system, assuming a suitable transducer configuration can be found that is able to operate at higher temperatures. Further investigation will study the possibility of using Piezoelectric Wafer Active Sensors (PWAS) or waveguides for this application.